Analisis Deskriptif Pengelolaan Kelas melalui Pendekatan Perubahan Perilaku - Dhiya, Muhammad; Sayekti, Siskha Putri; Bana, Naailatul; Nurmaulida, Nida (Ikatan Dai Indonesia, 2023)
The behavior change approach has the potential to increase interest in learning. This study uses a qualitative descriptive method with an open observational approach. Observations were made at MI Al-Hidayah Cipayung school. The main observational findings state two core points: (1) Rewards can improve performance and the form can be in the form of simple appreciation (2) Punishment can bring benefits and the form does not have to be in the form of punishment. The behavior change approach can make the classroom atmosphere more conducive and directed if it is applied properly.